SEBAB DAN DAMPAK PERKAWINAN PAKSA DI STASI REWUNG PAROKI SANTA MARIA PENOLONG ABADI LAWIR KEUSKUPAN RUTENG DAN IMPLIKASI PASTORALNYA - Avensius Labur; Fransiska Widyawati (Bahasa Indonesia, 2022)
A Catholic marriage is valid if it has complied with applicable laws. One of the legal rules is if the wedding is done based on love and the partner's free will. On the other hand, forced marriage is invalid. Forced marriage has many adverse effects, including it can lead to divorce or separation. This study conducted a study on separated/divorced couples at the Rewung Station of the St. Maria Penolong Abadi Parish in Lawir Diocese of Ruteng. The main focus and objective of the research are to analyze the causes and effects of forced marriages in the area. This study found the factors causing forced marriages, namely: marriage due to arranged marriages by parents, marriage due to arranged marriages in a large family as part of the marriage culture within the clan and already pregnant. The effects of forced marriages are squabbles or disharmony, domestic violence (KDRT), and divorce/separation. This study concludes that forced marriage is not only against the nature of the sacramental union of the Catholic Church but also has a destructive impact on the family and the Church itself. This study recommends that marriage preparation be carried out correctly in the premarital canonical and pastoral investigation process. Likewise, pastoral care for Catholic families also needs serious attention.